2013
DOI: 10.2147/ott.s49148
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits viability of pancreatic cancer stem cells in culture and in a xenograft model via binding to SHH-Gli

Abstract: ObjectiveOverexpression of the sonic hedgehog (SHH) signaling pathway is an essential characteristic of pancreatic cancer stem cells (PCSCs) and arsenic trioxide (ATO) is described as a SHH inhibitor. This study evaluates whether ATO has the potential to inhibit viability of PCSCs via binding to SHH-Gli proteins.MethodsCell counting kit-8 and flow cytometry were used for analyzing apoptosis in cells in vitro. The animal model was an athymic nude mouse model bearing subcutaneous xenografts of SW1990 pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…We have previously shown, and also demonstrate here, that short and long-term exposure to arsenic activates GLI signaling. However, a number of other groups have argued that arsenic attenuates GLI signaling rather than activates it (Fei et al, 2010;Kim et al, 2010Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). We now show, in agreement with these previous groups, that arsenic can also antagonize GLI/HH signaling.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have previously shown, and also demonstrate here, that short and long-term exposure to arsenic activates GLI signaling. However, a number of other groups have argued that arsenic attenuates GLI signaling rather than activates it (Fei et al, 2010;Kim et al, 2010Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). We now show, in agreement with these previous groups, that arsenic can also antagonize GLI/HH signaling.…”
Section: Discussionsupporting
confidence: 92%
“…We further showed that arsenic exposure levels are positively associated with HH pathway activity in human bladder cancer, a malignancy previously linked to chronic arsenic exposure (Fei et al, 2010). More recently, other reports have shown that arsenic inhibits HH signaling initiated by either HH treatment or high GLI levels, and researchers concluded that arsenic is a functional inhibitor of HH/GLI signaling (Kim et al, 2010(Kim et al, , 2013Beauchamp et al, 2011;Han et al, 2013;Nakamura et al, 2013;Yang et al, 2013;You et al, 2014). Here, we provide in vitro and in vivo evidence suggesting that arsenic can both activate and inhibit GLI signaling, with the direction of GLI modulation dictated primarily by the starting levels of intrinsic GLI activity.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, most of Hh antagonists target Smo receptor and little target the signaling components down-stream of Smo, such as fused homolog (Sufu) or GLI [50,51]. A few recent studies have demonstrated that ATO interferes with GLI proteins in the context of a dysregulated Hh signaling pathway in many human cancers, including malignant rhabdoid tumors, pancreatic cancer stem cells, acute promyelocytic leukemia, osteosarcoma and medulloblastoma [24][25][26][27]52]. Importantly, the study of Beauchamp has shown that the underlying mechanism of the anti-tumor effect of ATO is likely through direct binding and inhibition of GLI1 and/or GLI2 transcriptional activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…These evidences strongly raise the possibility of the application of ATO in teatment of PCa. A few studies have reported that ATO could inhibit tumor cell growth by blocking Hh pathway in rhabdoid tumor, osteosarcoma, Ewing sarcoma, pancreatic cancer stem cells and APL patients [24][25][26][27][28][29]. Furthermore, ATO has been established as a Hh pathway inhibitor [29] and a promising anti-tumor agent for Hedgehog-driven cancers [30].…”
mentioning
confidence: 99%